Treatment of ruptured blister-like aneurysms with the FRED flow diverter: a multicenter experience - Möhlenbruch, Markus Alfred; Seker, Fatih; Özlük, E.; Kizilkilic, O.; Broussalis, E.; Killer-Oberpfalzer, M.; Griessenauer, C. J.; Bendszus, Martin; Kocer, N. (American journal of neuroradiology, 2020)
BACKGROUND AND PURPOSE: Treatment of ruptured blister-like aneurysms is technically challenging. This study aimed at analyzing the safety and efficacy of the Flow-Redirection Endoluminal Device (FRED) in the treatment of ruptured blister-like aneurysms. - MATERIALS AND METHODS: In a retrospective multicenter study, all patients treated with the FRED due to a ruptured intracranial blister-like aneurysm between January 2013 and May 2019 were analyzed. The primary end points for clinical safety were mRS 0-2 at 6 months after treatment and the absence of major ipsilateral stroke or death. The primary end points for efficacy were the absence of rebleeding after treatment and complete angiographic occlusion according to the O’Kelly-Marotta classification at 6 months after treatment. - RESULTS: In total, 30 patients with 30 ruptured blister-like aneurysms were treated. Immediate complete aneurysm obliteration (O’Kelly-Marotta classification D) with the FRED was achieved in 10 patients (33%). Of the 26 patients with follow-up, complete obliteration was achieved in 21 patients (80%) after 6 months and in 24 patients (92%) in the final follow-up (median, 22 months). Twenty-three patients (77%) achieved mRS 0-2 at 6 months. Major stroke or death occurred in 17%. Two patients died due to pneumonia, and 2 patients died due to infarction following cerebral vasospasm. There was no case of rebleeding after FRED implantation. There was 1 case of delayed asymptomatic stent occlusion. - CONCLUSIONS: Treatment of ruptured blister-like aneurysms with the FRED is safe and effective.
Gesehen am 01.03.2021
DOI funktioniert nicht